2016
DOI: 10.1177/0886260516669168
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic Traits and the Cheater–Hawk Hypothesis

Abstract: The present study was a direct test of the cheater-hawk hypothesis which argues that psychopathy is related to two potentially adaptive interpersonal strategies: cheating and aggression. As expected, the measures of cheater and hawk behaviors comprised a single factor, according to a maximum-likelihood factor analysis. As hypothesized, psychopathic traits exhibited large positive correlations with measures of both cheater (entitlement, exploitiveness, and short-term mating orientation) and hawk (vengeance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Moreover, research has also found that psychopathic traits are correlated with deception in many domains (Seto et al 1997), and that psychopaths are more exploitive and aggressive than their nonpsychopathic counterparts (Book et al 2016a). Empirical findings also indicate that psychopathic traits are associated with the use of intimidation and aggression, and are negatively associated with altruistic behavior (Book and Quinsey 2004;Book et al 2016a). Because of these consistent relationships, Book and colleagues (2016a) have suggested that psychopathy is an adaptation for social predation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, research has also found that psychopathic traits are correlated with deception in many domains (Seto et al 1997), and that psychopaths are more exploitive and aggressive than their nonpsychopathic counterparts (Book et al 2016a). Empirical findings also indicate that psychopathic traits are associated with the use of intimidation and aggression, and are negatively associated with altruistic behavior (Book and Quinsey 2004;Book et al 2016a). Because of these consistent relationships, Book and colleagues (2016a) have suggested that psychopathy is an adaptation for social predation.…”
mentioning
confidence: 99%
“…This has clear evolutionary advantages, allowing resource procurement and reproductive success with minimal investment. More specifically, in the language of game theory, psychopaths can be seen as being both ''cheaters'' and ''warrior-hawks''; in other words, ''cheater-hawks'' (Book and Quinsey 2004;Book et al 2016a). Cheaters use manipulation and deception to exploit the cooperation of others, while warrior-hawks use intimidation and aggression to get what they want (Dawkins 1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, psychopathy has been linked to having children at a younger age (Tielbeek et al, 2018), and having a greater number of children than non-psychopathic individuals (Međedović et al, 2017). These findings are consistent with the notion that the intimidating and manipulative traits of psychopathy allow for greater success exploiting others, including sexual or romantic exploitation resulting in reproductive success (Book et al, 2016;Meloy et al, 2018). This suggests an adaptive and reproductive function of psychopathy, which elucidates why psychopathic individuals are more likely to engage in sexually coercive and violent behaviours (Knight & Guay, 2006;O'Connell & Marcus, 2016).…”
Section: Psychopathysupporting
confidence: 65%
“…In previous studies, Benign Envy was associated with Machiavellianism and to a lesser extent with grandiose narcissism, while Malicious Envy was associated with both Machiavellianism and psychopathy from the Dark Triad (e.g., Lange, Paulhus, et al, 2018). Among HEXACO traits, Honesty-Humility could be seen as the "core" element of the Dark Tetrad (the Dark Triad + sadism, e.g., Book et al, 2016). Previous studies have shown that both forms of envy predict morally questionable behaviors (see Crusius et al, 2020), including those whose predisposition is Honesty-Humility, such as deception and manipulative interpersonal behavior.…”
Section: Studymentioning
confidence: 91%